Representasi Kekuatan, Kecerdasan, dan Cita Rasa Perempuan: Analisis Wacana pada Film “The Iron Lady” - Wahyuningtyas, Bhernadetta Pravita (Bina Nusantara University, 2014)
People’s perception about women describes how women tend to be labelized with various drawbacks. Futhermore, many films put women as appendages to satisfy the desire of seeing the physical polish only, without portraying positive side of a woman which actually represents her personal integrity. Nevertheless, the struggle of women to prove their existence is unstoppable, such as in “The Iron Lady” movie. The movie intends to persuade women that they need to pump out the power within them to boldly express their thoughts, come out from the mutedness and show their superiority, in smart ways, woman way. Besides, the movie shows some gender imbalances in Parliament and political life which are synonymous with patriarchal ideology. The movie also shows the struggle against the suppression and mutedness of women with the feminist existentialist concept. This study used critical paradigm with Roland Barthes’ semiotic discourse analysis. Research reveals how women represented in